2012
DOI: 10.1590/s0036-46652012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of peritoneal macrophage from different species of neotropical primates to Ex vivo Leishmania (L.) infantum chagasi-infection

Abstract: This study examined the susceptibility of peritoneal macrophage (PM) from the Neotropical primates: Callithrix jacchus, Callithrix penicillata, Saimiri sciureus, Aotus azarae infulatus and Callimico goeldii to ex vivo Leishmania (L.) infantum chagasi-infection, the etiological agent of American visceral leishmaniasis (AVL), as a screening assay for evaluating the potential of these non-human primates as experimental models for studying AVL. The PM-susceptibility to infection was accessed by the PM-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…(Marsden et al 1981, Dietze et al 1985. However, according to Carneiro et al (2012), they are considered inadequate biological models for the study of VL, because they are able to inhibit experimental infections by L. (L.) infantum. The orange-spined hairy dwarf porcupine (S. villosus) belongs to the Family Erethizontidae, the same family of Rothschild's porcupine (Coendou rothschildi), species to which natural infections by another Leishmania species, L. (L.) hertigi (Herrer 1971), have been attributed, including in Brazil (Silva et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(Marsden et al 1981, Dietze et al 1985. However, according to Carneiro et al (2012), they are considered inadequate biological models for the study of VL, because they are able to inhibit experimental infections by L. (L.) infantum. The orange-spined hairy dwarf porcupine (S. villosus) belongs to the Family Erethizontidae, the same family of Rothschild's porcupine (Coendou rothschildi), species to which natural infections by another Leishmania species, L. (L.) hertigi (Herrer 1971), have been attributed, including in Brazil (Silva et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Aotus griseimembra is highly susceptible to Plasmodium falciparum; A. nancymaae is less susceptible to some strains and resistant to others (Schmidt, 1978). Owl monkeys have also served as a model for cutaneous and visceral leishmaniasis (Chapman et al, 1981;Broderson et al, 1986), although a more recent study suggests that owl monkeys have developed resistance against Leishmania infantum chagasi via innate immune response mechnanisms which may limit its use with this pathogen (Carneiro et al, 2012). are susceptible to P. vivax (Schmidt, 1978).…”
Section: Research Usesmentioning
confidence: 99%
“…As indicated in a study conducted by Carneiro et al [ 21 ], these infected primates were clinically healthy. Carneiro et al hypothesized that New World primates have developed an innate immune response mechanism capable of controlling macrophage intracellular growth of L. infantum [ 21 ]. However, several field studies have confirmed a high susceptibility to Leishmania spp.…”
Section: Discussionmentioning
confidence: 69%